2018
DOI: 10.1089/gtmb.2017.0072
|View full text |Cite
|
Sign up to set email alerts
|

Associations of IL-1, 6, and 10 Gene Polymorphisms with Susceptibility to Recurrent Aphthous Stomatitis: Insights from a Meta-Analysis

Abstract: The IL-1b+3954 C/T polymorphism significantly increases RAS risk. In addition, the IL-10-1082 G/A polymorphism provided protective effects for RAS in the Asian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Many inflammatory mediators, including IL-1, IL-2, IL-17, and IL-18, have been investigated in RAS [17,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Many inflammatory mediators, including IL-1, IL-2, IL-17, and IL-18, have been investigated in RAS [17,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Sustained and excessive IL‐6 production can disrupt the cytokine network and lead to oral mucosal damage, which eventually leads to mucosal lesions in RAS. In recent years, more studies on IL‐6 had turned to gene polymorphism, several meta‐analysis showed that the IL‐6‐174 G/C polymorphism did not have a statistically significant association with RAS susceptibility, 14,15 whereas there was also a study showed individuals with the G allele and GG genotype of IL‐6‐174 appeared to be more vulnerable to developing RAS 16 . Therefore, the role of IL‐6 and IL‐17A in RAS remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of these pro-inflammatory cytokines was confirmed by many studies that investigated the clinical significance of serum IL-6, IL-1, and TNF-α in RAS. [ 6 23 , 24 ] Results of these studies revealed that the levels of serum IL-1, IL-6, and TNF-α in RAS patients were significantly increased.…”
Section: Discussionmentioning
confidence: 99%